Democracy Model Based on Bali Local Wisdom Values for Capacity Building of Regional Governance - Suacana, I Wayan Gede; Suaib, Eka (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
This research was conducted applying qualitative method for assessing governance in Bali Region. The stage of research began with the collection of primary and secondary data. The second stage was choosing a theory as means of analyzing the data. The third stage analyzed and interpreted the data that had been selected. The fourth stage was to do the writing and construction of research results. The results showed that values of local wisdom of Bali, which is reflected in its democratic models, showed how the government and people of Bali held a governance rule. Strengthening institutional capacity and the capacity of policy was strongly supported by the development of this democratic model. In this context, there is a symmetrical relationship between the accountability and transparency of government who is regarded as Guru Wisesa with the level of public trust in him. It is also supported by the implementation of the five values of local wisdom in giving service (seva) to the public, namely: Sathya (Truth), Dharma (virtue), Shanti (Peace), Prema (love) and Ahimsa (abstinence violence). However, the model of democracy with the values of local wisdom is not enough to produce a democratic political system without the support of the situation, conditions and political institutions. Freedom and equality (equality) as part of the democratic values are still hampered by paternalistic cultures that restrict the freedom of society.